2004
DOI: 10.1016/j.biolcel.2004.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila cohesins DSA1 and Drad21 persist and colocalize along the centromeric heterochromatin during mitosis

Abstract: Sister chromatid cohesion in eukaryotes is maintained mainly by a conserved multiprotein complex termed cohesin. Drad21 and DSA1 are the Drosophila homologues of the yeast Scc1 and Scc3 cohesin subunits, respectively. We recently identified a Drosophila mitotic cohesin complex composed of Drad21/DSA1/DSMC1/DSMC3. Here we study the contribution of this complex to sister chromatid cohesion using immunofluorescence microscopy to analyze cell cycle chromosomal localization of DSA1 and Drad21 in S2 cells. We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…This confirms the results of a recent study using ectopic expression of TEV protease to remove an engineered Rad21 protein during early embryonic development (8). These findings come as no surprise in light of previous work in other eukaryotes and less direct studies in Drosophila involving Rad21 localization and RNAi knockdown approaches (16,17), but they are satisfying and important results nonetheless.…”
Section: Identification Of Verthandi a Heterochromatic Gene That Encsupporting
confidence: 87%
“…This confirms the results of a recent study using ectopic expression of TEV protease to remove an engineered Rad21 protein during early embryonic development (8). These findings come as no surprise in light of previous work in other eukaryotes and less direct studies in Drosophila involving Rad21 localization and RNAi knockdown approaches (16,17), but they are satisfying and important results nonetheless.…”
Section: Identification Of Verthandi a Heterochromatic Gene That Encsupporting
confidence: 87%
“…Thus, the studies reported in this paper provide no information regarding the binding of cohesin or Nipped-B binding to centromeres. By immunostaining, cohesin binds to both mitotic and meiotic centromeres in Drosophila (Warren et al 2000;Valdeolmillos et al 2004;Khetani and Bickel 2007;Gause et al 2007). Immunostaining with the same Nipped-B antibody used in the experiments reported in this paper indicates that Nipped-B colocalizes with cohesin along chromosome arms in both polytene and meiotic chromosomes, but not at centromeres in meiotic chromosomes (Gause et al 2007).…”
Section: Discussion Cohesin Localization Differs Between Yeast and Drmentioning
confidence: 63%
“…These results do not mean, however, that repetitive sequences are generally cohesin-poor. By immunostaining, cohesin binds the pericentric heterochromatin of both mitotic and meiotic chromosomes in Drosophila (Warren et al 2000;Valdeolmillos et al 2004;Khetani and Bickel 2007;Gause et al 2007). …”
Section: Nipped-b and Cohesin Colocalize Genome-widementioning
confidence: 99%
“…Nipped-B, however, also does not colocalize with the HP1 heterochromatin protein, whose Swi6 ortholog in S. pombe is required for cohesion and interacts with cohesin (Bernard et al 2001;Nonaka et al 2002), at positions that are not under-replicated. In cultured Drosophila cells, Rad21 and SA persist at the centromeres until the metaphase-anaphase transition (Valdeolmillos et al 2004;Warren et al 2000). We have immunostained metaphase chromosome spreads from Kc cells and can see Smc1 and SA that colocalizes with the CID centromere-specific histone at centromeres but have not been able to detect Nipped-B (Gause and Dorsett, unpublished).…”
Section: Does Nipped-b Regulate Cohesin Function At Centromeres?mentioning
confidence: 98%